Associations between fractional anisotropy and problematic alcohol use in juvenile justice-involved adolescents. (4th November 2013) - Thayer, Rachel E.; Callahan, Tiffany J.; Weiland, Barbara J.; Hutchison, Kent E.; Bryan, Angela D.
Abstract: Background : Studies have shown associations between heavy alcohol use and white matter alterations in adolescence. Youth involved with the juvenile justice system engage in high levels of risk behavior generally and alcohol use in particular as compared to their non-justice-involved peers. Objectives : This study explored white matter integrity among justice-involved adolescents. Analyses examined fractional anisotropy (FA) and mean diffusivity (MD) between adolescents with low and high levels of problematic alcohol use as assessed by the Alcohol Use Disorders Identification Test (AUDIT). Methods : Participants ( N  = 125; 80% male; 14–18 years) completed measures assessing psychological status and substance use followed by diffusion tensor imaging (DTI). DTI data for low ( n  = 51) and high AUDIT ( n  = 74) adolescents were subjected to cluster-based group comparisons on skeletonized FA and MD data. Results : Whole-brain analyses revealed significantly lower FA in clusters in the right and left posterior corona radiata (PCR) and right superior longitudinal fasciculus (SLF) in the high AUDIT group, as well as one cluster in the right anterior corona radiata that showed higher FA in the high AUDIT group. No differences in MD were identified. Exploratory analyses correlated cluster FA with measures of additional risk factors. FA in the right SLF and left PCR was negatively associated with impulsivity. Conclusion : Justice-involved adolescents with alcohol use problems generally showed poorer FA than their low problematic alcohol use peers. Future research should aim to better understand the nature of the relationship between white matter development and alcohol use specifically as well as risk behavior more generally.